2015
DOI: 10.3126/jonmc.v3i1.12235
|View full text |Cite
|
Sign up to set email alerts
|

A Household Survey on Awareness of Hiv/Aids Among Rural People of Chandbela Vdc Of Eastern Nepal

Abstract: Abstract:Background: In the past 20 years HIV/AIDS has become an increasing global phenomenon. The rising trend of morbidity and mortality has not only changed the demography but also poses a huge socio-economic burden on well-being of households, communities and country. In Nepal as the epidemic is maturing. However, the epidemic has never been maintained in the general population through heterosexual transmission in Nepal, rather it is driven by the infections among higher risk populations and their sexual p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
(3 reference statements)
0
0
0
Order By: Relevance
“…The government of Nepal recorded 1,610 cases of AIDS and 10,546 HIV infections as of December 2007, whereas UNAIDS estimates from 2005 indicated that roughly 7,500 persons in Nepal were HIV positive. In December 2015, the National Center for AIDS and STD Control (NCASC) predicted a higher total of over 70,000 (Khanal, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The government of Nepal recorded 1,610 cases of AIDS and 10,546 HIV infections as of December 2007, whereas UNAIDS estimates from 2005 indicated that roughly 7,500 persons in Nepal were HIV positive. In December 2015, the National Center for AIDS and STD Control (NCASC) predicted a higher total of over 70,000 (Khanal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The profound danger of AIDS lies in its universal susceptibility, leading to inevitable fatality. Consequently, exercising caution in selecting safe sexual partners is imperative to avoid severe consequences (Khanal, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation